Mutant ASXL1 cooperates with BAP1 to promote myeloid leukaemogenesis - Shuhei Asada (Nature Portfolio, 2018)
ASXL1 gene is often mutated in myeloid malignancies. Here, the authors show that mutant ASXL1 and BAP1 are in a positive feedback loop such that BAP1 induces monoubiquitination of mutant ASXL1, which in turn enhances BAP1 activity to potentiate myeloid transformation via HOXA clusters and IRF8.